Fauna, Ecological Characteristics, and Checklist of the Mosquitoes in Mazandaran Province, Northern Iran. Issue 3 (6th January 2018) - Nikookar, Seyed Hassan; Fazeli-Dinan, Mahmoud; Azari-Hamidian, Shahyad; Nasab, Seyed Nouraddin Mousavi; Aarabi, Mohsen; Ziapour, Seyyed Payman; Enayati, Ahmadali; Hemingway, Janet
Abstract: Mosquitoes are important vectors of human and animal diseases. This study updates current knowledge on fauna, dominance, and distribution of mosquitoes in Mazandaran Province, Northern Iran, to inform disease control effort. Larval collections, using standard dippers or droppers, and adult collections, using total catches, shelter pits, CDC light traps, and human landing catches, were performed monthly in 30 villages across 16 counties, from May to December 2014. Ovitraps, baited with hay infusion as oviposition attractants or stimulants for Aedes ( Stegomyia ) mosquitoes, were installed in each village and inspected weekly for eggs. Lactophenol and Berlese media were used for preserving and mounting specimens. Overall, 36, 024 mosquito specimens (19, 840 larvae and 16, 184 adults) belonging to 4 genera and 20 species were morphologically identified. The dominance and distribution indices showed that Culex pipiens s.s. was the eudominant species with a constant distribution of larvae ( D = 69.07%, C = 100%) and adults ( D = 31.86%, C = 100%), followed by Cx tritaeniorhynchus ( D = 38.14%, C = 100%) and Anopheles maculipennis s.l. ( D = 11.05%, C = 100%) as adults. Aedes vexans was the dominant (7.85%) species, but it had a sporadic (20%) distribution. Culex torrentium and Culiseta morsitans were added as the new species to the checklist of mosquitoes in Mazandaran Province. Due to the potential role, Cx. pipiens s.s. as a vector of various pathogens, further ecological studies are recommended.